2015
DOI: 10.2174/1874364101509010049
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Surface as Barrier of Innate Immunity

Abstract: Sight is one of the most important senses that human beings possess. The ocular system is a complex structure equipped with mechanisms that prevent or limit damage caused by physical, chemical, infectious and environmental factors. These mechanisms include a series of anatomical, cellular and humoral factors that have been a matter of study. The cornea is not only the most powerful and important lens of the optical system, but also, it has been involved in many other physiological and pathological processes ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 112 publications
0
28
0
2
Order By: Relevance
“…Eye is protected by epithelia and mucous membranes which both serve as mechanical, chemical and biological barriers against pathogens (Bolaños-Jiménez et al, 2015). Tearing is an innate immunity mechanism that *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Eye is protected by epithelia and mucous membranes which both serve as mechanical, chemical and biological barriers against pathogens (Bolaños-Jiménez et al, 2015). Tearing is an innate immunity mechanism that *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…MIGS are ab interno procedures requiring minimal to no conjunctival manipulation or scleral dissection, which can be safely performed at the time of another intraocular procedure, specifically cataract extraction by phacoemulsification. They improve aqueous outflow, as traditional filtering surgeries do, but typically to a more modest degree than trabeculectomy or tube shunt implantation and with fewer risks than those more invasive surgeries (Caprioli 2015; Francis 2011; Spaeth 2015). While MIGS interventions are not generally used as first-line therapy at this time, they may reduce the need for medication.…”
Section: Introductionmentioning
confidence: 99%
“…topical eye drops) as first line of therapy (AAO 2015; NICE 2009), commercially available eye drops have short durations of effect and notoriously poor adherence (Friedman 2009; Okeke 2009). Conventional surgical procedures to alter the trabecular meshwork and drainage angle (such as trabeculectomy) and tube shunts or valves are associated with variable frequencies of success and complications (Gedde 2012a; Gedde 2012b; Spaeth 2015). Several studies have suggested that trabeculectomies fail after about five years in approximately 50%of cases (Gedde 2012a;Gedde 2012b; Kirwan 2013; Lichter 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Esta complexa estrutura é responsável pela nutrição, imunidade e proteção mecânica, da interface ocular com o meio ambiente. Contribui para uniformização e hidratação da superfície epitelial corneana, auxiliando na refração 72 .…”
Section: Superfície Ocular Filme Lacrimal E Técnicas De Coleta De Láunclassified
“…Esta é uma característica da resposta imune das mucosas e, portanto, similar a outras interfaces mucosas do corpo humano. Sendo assim, sob condições normais, a presença de IgA secretória, células linfoides e células dentrídicas favorecem um predomínio de resposta imune humoral e pouco citotóxica 72 .…”
Section: Superfície Ocular Filme Lacrimal E Técnicas De Coleta De Láunclassified